Screening for viruses associated with myocarditis and genotyping human parvovirus B19 in cases of sudden and unexpected death in Infancy (SUDI) at Tygerberg Medico-Legal Mortuary - Ngobeni, Trevor (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.